Gamma radiation in roselle seeds to induce morphological variation and selection of mutants - Gálvez-Marroquín, Luis Antonio; Avendaño-Arrazate, Carlos Hugo; Ariza-Flores, Rafael; Gomez-Simuta, Yeudiel; Martínez-Bolaños, Misael; Cruz-López, Jesús Alberto (Revista Mexicana de Ciencias Agrícolas, 2023)
The objective was to determine the LD50 and RC50 and induce morphological variation in the roselle variety UAN-8 by gamma rays to select mutant plants of agronomic interest in the M2 generation. The radiation doses used were: 0, 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1 000 Gy. The experiments were conducted under greenhouse and field conditions in Río Grande, Villa de Tututepec, Oaxaca, in 2018. The experimental design used was randomized blocks with four repetitions. In M1, seedling emergence, survival, height and percentage of plants were evaluated. In M2, morphological variation was recorded, and mutant plants were selected. Plant survival and height data were analyzed using nonlinear regression to determine the median lethal and reductive doses (LD50 and RC50). The LD50 and RC50 were found at 395.48 and 453.2 Gy, respectively. The M2 seeds of this variety produced plants with morphological variability in doses from 100 to 300 Gy. From these plants, it was possible to identify six promising mutant genotypes. The genotype identified as S7 L13 presented desirable morphological characteristics such as a higher number of red calyces per plant and absent or very weak pubescence, compared to the plants of the parental genotype.
Keywords: gamma radiation; mutagenesis; radiosensitivity